2012
DOI: 10.1029/2011ja017155
|View full text |Cite
|
Sign up to set email alerts
|

A statistical study of magnetopause structures: Tangential versus rotational discontinuities

Abstract: A statistical study of the structure of Earth's magnetopause is carried out by analyzing two‐year AMPTE/IRM plasma and magnetic field data. The analyses are based on the minimum variance analysis (MVA), the deHoffmann‐Teller (HT) frame analysis and the Walén relation. A total of 328 magnetopause crossings are identified and error estimates associated with MVA and HT frame analyses are performed for each case. In 142 out of 328 events both MVA and HT frame analyses yield high quality results which are classifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 38 publications
(69 reference statements)
3
19
0
Order By: Relevance
“…Only 18, respectively, 14 of these crossings, had Walén regression slopes above 0.5. These fractions of cases indicating an RD‐like magnetopause are comparable to the results reported by Chou and Hau () and only slightly higher than the Cluster results in Haaland et al (). For comparison, the MMS dayside study by Paschmann et al () found Walén slopes above 0.5 in around 30% of the cases.…”
Section: Resultssupporting
confidence: 89%
“…Only 18, respectively, 14 of these crossings, had Walén regression slopes above 0.5. These fractions of cases indicating an RD‐like magnetopause are comparable to the results reported by Chou and Hau () and only slightly higher than the Cluster results in Haaland et al (). For comparison, the MMS dayside study by Paschmann et al () found Walén slopes above 0.5 in around 30% of the cases.…”
Section: Resultssupporting
confidence: 89%
“…The change of V x , V y , and V z are in phase (antiphase) with the corresponding magnetic field components on the B z < 0 (B z > 0) side. Such spatial structures are consistent with being rotational discontinuities, or large-amplitude Alfvén waves, as have been found in previous 1-D and 2-D simulations and statistical studies [Lin and Swift, 1996;Lee et al, 1996;Chou and Hau, 2012].…”
Section: Case 3: Infinite X Line Length Finite Guide Fieldsupporting
confidence: 91%
“…For various reasons, including pressure anisotropy and composition effects (see discussion in, e.g., Paschmann and Sonnerup [] about this), values close to unity are rarely observed, however. Both Paschmann et al [] and Chou and Hau [] therefore classified cases with Walén slopes greater than 0.5 as RDs. We will adapt these thresholds also for classifications of our events.…”
Section: Characteristics Of the Magnetopause Flanksmentioning
confidence: 99%